Self-Reported Population Health : an International Perspective Based on EQ-5D. - Szende, Agota; Janssen, Bas.; Cabases, Juan. (Dordrecht : Springer Netherlands, 2013)
The EQ-5D survey enables vital transnational comparisons to be made on self-assessed health. This volume has an unprecedented range of tabulated data from the 24 participating nations, and includes clear explanations as well as guidance for users.
Intro -- The EuroQol Group -- Acknowledgements -- Contents -- Glossary of EQ-5D Terms -- Contributors -- Chapter 1: Introduction -- 1.1 Purpose of This Book -- 1.2 EQ-5D -- 1.3 The Structure of the Book -- Chapter 2: Data and Methods -- 2.1 International EQ-5D Archive of Population Surveys -- 2.2 Methods of Describing EQ-5D Population Norms -- 2.3 Methods of Cross-Country Analysis of EQ-5D Data -- 2.4 Methods of Sociodemographic Analysis of EQ-5D Data -- Chapter 3: Population Norms for the EQ-5D -- 3.1 Catalogue of Population Norms -- 3.2 EQ VAS Population Norms -- 3.3 EQ-5D Dimensions -- 3.4 EQ-5D Index Population Norms -- Chapter 4: Cross-Country Analysis of EQ-5D Data -- 4.1 Cross Country Comparison of Standardized EQ-5D Data -- 4.2 The Impact of Economic and Health Care Indicators -- Chapter 5: Socio-demographic Indicators Based on EQ-5D -- 5.1 The Use of EQ-5D in Socio-demographic Analysis -- 5.2 Odds Ratios Based on EQ-5D -- 5.3 Concentration Indices Based on EQ-5D -- 5.4 Conclusions -- Annex 1: EQ-5D Population Norms - National Surveys -- Annex 2: EQ-5D Population Norms - Regional Surveys -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books